Evaluasi Analisis Beban Kerja (E-ABK) di Badan Pendapatan Daerah Kota Surabaya - Nabiilah, Luthfiyyah; Kalvin Edo Wahyudi (VISA: Journal of Vision and Ideas, 2024)
One form of bureaucratic reform is a change in government activities that utilizes technology as a means of implementing a program or policy. Workload analysis is a policy used to calculate the workload of a government agency. Analysis of the implementation of workload in the Surabaya City Government using the ABK or e-ABK website so that this research was carried out to start implementing e-ABK in one of the regional apparatus of the Surabaya City Government, namely the Regional Revenue Agency (Bapenda). This research is descriptive qualitative research conducted by interviews and direct observation with related parties. The research results show that the evaluation of the implementation of e-ABK in the Surabaya City Bapenda has gone well based on five evaluation policy indicators according to William Dunn which include effectiveness, adequacy, equity, responsiveness and accuracy. Improvements to e-ABK by the Organization Section of the Surabaya City Regional Secretariat as the implementer of the workload analysis policy are a consideration in evaluating the implementation of workload analysis in the Surabaya City Government.